Molecular aspects of bladder cancer - Amorim,Gelbert Luiz Chamon do Carmo (2011)
ABSTRACT One of the most important objectives of genetic markers of cancer will be the possible identification of individuals at greatest risk in order to allow better management and prognosis. Many urological tumors were associated to various types of gene alterations with a great number of genes involved in the process, hindering gene therapy. This treatment uses specific techniques and one or several genes are manipulated in the laboratory in order to induce molecular alterations that may block the oncogenic process. The article addresses these issues emphasizing the importance of the new molecular biology techniques.